Pengaruh Komposisi Media Tanam dan ZPT Air Kelapa terhadap Pertumbuhan setek pucuk Jeruk Kacang (Citrus reticulata Blanco). - Rivo Yulse Viza; Arista Ratih (Universitas Andalas, 2018)
‘Limau kacang’ has been a specialty crop in the Solok region of West Sumatra. The spread of Citrus reticulata Blanco is still experiencing barriers and the population is threatened with extintion. Overcome the problem is done propagation of Citrus reticulata Blanco vegetatively with shoot cutting. The experiment on the influence of different growing media and hormonal growth of coconut water to the shoot cutting of Citrus reticulata Blanco has been accomplished at kanagarian Kacang Kecamatan X Koto Singkarak, Kabupaten Solok, this experiment started in June to October 2017. This research used Randomized Completely Block Design (RCBD) Factorial. The first factor was four different growing media (soil, soil : manure, soil : husk, soil : sand) while the second factor was two level coconut water concentrations (0% and 25%) with three replication. Variables analiyzed were the survival percentage, while emerging shoots, shoot length, number of leaf, number of shoot, number of root and root length. The result of this research showed that A3B0 treatment (planting media soil : manure without coconut water as hormonal growth) gave the best influence to the growth of shoot cuttings of Citrus reticulata Blanco.